Melatonin Priming Increases the Tolerance of Tartary Buckwheat Seeds to Abiotic Stress - Liwei Zhu; Guohong Tang; Xiaoyu An; Hongyou Li; Qingfu Chen (Agronomy, 2025)
Increasing abiotic stress, particularly salinity, poses a significant threat to the germination and seedling development of Tartary buckwheat, thereby limiting its yield potential and broader cultivation. Given Tartary buckwheat’s rich nutritional profile and inherent stress adaptability, enhancing seed tolerance to abiotic stress is essential for ensuring food security and the development of functional food resources. To investigate the role of melatonin in mitigating abiotic stress, seeds of the cultivar ‘Jinqiaomai 2’ were primed with varying melatonin concentrations (with water as the control) at multiple time points. The effects of salt stress on germination and seedling quality were evaluated to determine optimal priming conditions. Subsequent analyses examined seed vigor and physiological and biochemical responses during storage under high temperature and humidity, room temperature, and low-temperature conditions. The results showed that a 3 h melatonin priming consistently resulted in high germination rates (98.7–100.0%). Notably, melatonin at 50 μmol·L−1 was identified as the optimal concentration, significantly improving seedling growth under salinity stress, with increases of 61.1% in seedling length, 59.3% in root length, and 38.9% in root fresh weight compared with the control. Across all storage environments, melatonin-primed seeds exhibited superior vigor and enhanced antioxidant enzyme activity relative to water-primed controls. In conclusion, melatonin priming at an appropriate concentration and duration effectively enhanced the vigor of Tartary buckwheat seeds and alleviated the adverse effects of salinity on germination and storage resilience. However, improved seeds may possess a limited safe storage window and should be sown promptly rather than stored long-term.